Stereospecific micellar electrokinetic chromatography assay of methionine sulfoxide reductase activity employing a multiple layer coated capillary. Issue 18 (9th August 2013) - Zhu, Qingfu; El‐Mergawy, Rabab G.; Heinemann, Stefan H.; Schönherr, Roland; Jáč, Pavel; Scriba, Gerhard K. E.; Kašička, Václav
<x xml:space="preserve">Abstract</x> A micellar electrokinetic chromatography method for the analysis of the l‐methionine sulfoxide diastereomers employing a successive multiple ionic‐polymer layer coated fused‐silica capillary was developed and validated in order to investigate the stereospecificity of methionine sulfoxide reductases. The capillary coating consisted of a first layer of hexadimethrine and a second layer of dextran sulfate providing a stable strong cathodic EOF and consequently highly repeatable analyte migration times. The methionine sulfoxide diastereomers, methionine as product as well as β‐alanine as internal standard were derivatized by dabsyl chloride and separated using a 35 mM sodium phosphate buffer, pH 8.0, containing 25 mM SDS as BGE and a separation voltage of 25 kV. The method was validated in the range of 0.15–2.0 mM with respect to linearity and precision. The LODs of the analytes ranged between 0.04 and 0.10 mM. The assay was subsequently applied to determine the stereospecificity of methionine sulfoxide reductases as well as the enzyme kinetics of human methionine sulfoxide reductase A. Monitoring the decrease of the l‐methionine‐(S)‐sulfoxide Km = 411.8 ± 33.8 μM and Vmax = 307.5 ± 10.8 μM/min were determined.